Factors associated with patients' experience of accessibility to general practice: results from a national survey in Norway - Elma Jelin; Oyvind Bjertnaes; Rebecka Maria Norman (BMC, 2024)
Abstract Background This study aimed to explore the influence of patient-, general practitioners (GP)-, and GP practice-level predictor variables on patient-experienced accessibility to GPs and GP practices. Additionally, we aimed to enhance our understanding of patient-experienced accessibility by analysing the free-text comments from patients who reported lowest accessibility scores to GPs and GP practices. Methods We performed a secondary analysis of data from a 2021-2022 national Norwegian survey on patient experiences with their GP and GP practice. We identified seven accessibility-related items including experience and acceptance of regular waiting time and for urgent appointments, time spent with the GP, waiting time in the wating-room, and getting in touch with the GP practice by telephone. A composite accessibility score was computed. Predictor variables consisted of patient's self-reported characteristics, as well as background data about the GP and GP practice from National GP registry. The analysis included multiple linear regression of the composite accessibility score and seven accessibility items. Finally, a qualitative analysis was conducted of free-text survey comments among patients that had a score of 0 (unfavourable) on all the seven accessibility items. Results The key factor for patient-experienced accessibility to general practice was seeing their own GP, showing a statistically significant positive correlation (p<0.001) across all seven accessibility items and the composite accessibility score in regression analyses. Other associations with positive experience included better self-reported health, and at the GP-level, a specialization in general medicine. Conversely, a negative experience was associated with longer time since the last GP consultation, female patients, and a higher number of GPs at the practice. Qualitative data confirmed accessibility challenges, detailing quantitative scores and highlighted that low accessibility scores were related to difficulties in seeing one's own GP. Conclusions This study highlights the importance of continuity between patient and their GP in improving patients' experiences of accessibility to general practice. Several GP and GP practice-level factors were related to patient-reported accessibility. These results can be used to inform initiatives aimed at improving accessibility to general practice.